N02 Safety And Tolerability Of Selisistat For The Treatment Of Huntington's Disease: Results From A Randomised, Double-blind, Placebo-controlled Phase Ii Trial. (17th September 2014) - Reilmann, R; Squitieri, F; Priller, J; Saft, C; Mariotti, C; Süssmuth, SD; Nemeth, AH; Tabrizi, SJ; Quarrell, O; Craufurd, D; Rickards, H; Rosser, A; et al.
Abstract : Background: Selisistat is a first-in-class SirT1 inhibitor shown to be safe and well tolerated in healthy volunteers and HD patients in short-term studies. Objective: To evaluate safety and tolerability of selisistat over 12 weeks in patients with Huntington's disease (HD). Design/methods: This was a double-blind, placebo-controlled, international multi-centre study of selisistat in individuals with Stage I-III HD. Participants (30–70 yrs) with genetically confirmed HD, a Unified Huntington Disease Rating Scale (UHDRS) Total Motor Score of ≥ 5 and a Total Functional Capacity ≥ 5 were randomised (1:1:1) to selisistat 50 or 200 mg or placebo once daily for 12 weeks. Safety and tolerability were evaluated by monitoring adverse events, vital signs, ECG and laboratory safety data throughout the study. Blood sampling for pharmacokinetics and soluble mutant huntingtin levels were collected throughout. Results/outcome: A total of 144 patients were randomised and 125 patients (87%) completed the study. There were 9 serious adverse events, three in each treatment group, including one death in the placebo group. The most common adverse events were reversible increases in liver function tests without accompanying increases in bilirubin. All of these occurred in the selisistat groups; while most of these increases were <3×ULN, three events were classified as serious. No clinically relevant changes in the UHDRS readouts were observed during the relatively short treatment period. Levels of soluble mutant huntingtin in peripheral blood mononuclear cells showed borderline statistically significant (p = 0.058, p = 0.075) increases of similar magnitude at 12 weeks compared to placebo in the 50mg and 200mg groups respectively, that reverted to levels consistent with the placebo group at follow-up. Conclusions: Apart from increases in liver function tests in a subset of patients, selisistat was safe and well tolerated, and a trend for modulation of the levels of soluble mutant huntingtin was observed. Acknowledgement: Supported by Siena Biotech SpA.